Rational Development of Guanidinate and Amidinate Based Cerium and Ytterbium Complexes as Atomic Layer Deposition Precursors: Synthesis, Modeling, and Application. Issue 15 (20th January 2021) - Kaur, Parmish; Mai, Lukas; Muriqi, Arbresha; Zanders, David; Ghiyasi, Ramin; Safdar, Muhammad; Boysen, Nils; Winter, Manuela; Nolan, Michael; Karppinen, Maarit; Devi, Anjana
Abstract: Owing to the limited availability of suitable precursors for vapor phase deposition of rare‐earth containing thin‐film materials, new or improved precursors are sought after. In this study, we explored new precursors for atomic layer deposition (ALD) of cerium (Ce) and ytterbium (Yb) containing thin films. A series of homoleptic tris‐guanidinate and tris‐amidinate complexes of cerium (Ce) and ytterbium (Yb) were synthesized and thoroughly characterized. The C‐substituents on the N‐C‐N backbone (Me, NMe2, NEt2, where Me=methyl, Et=ethyl) and the N‐substituents from symmetrical iso‐propyl ( i Pr) to asymmetrical tertiary‐butyl ( t Bu) and Et were systematically varied to study the influence of the substituents on the physicochemical properties of the resulting compounds. Single crystal structures of [Ce(dpdmg)3 ] 1 and [Yb(dpdmg)3 ] 6 (dpdmg= N, N' ‐diisopropyl‐2‐dimethylamido‐guanidinate) highlight a monomeric nature in the solid‐state with a distorted trigonal prismatic geometry. The thermogravimetric analysis shows that the complexes are volatile and emphasize that increasing asymmetry in the complexes lowers their melting points while reducing their thermal stability. Density functional theory (DFT) was used to study the reactivity of amidinates and guanidinates of Ce and Yb complexes towards oxygen (O2 ) and water (H2 O). Signified by the DFT calculations, the guanidinates show an increased reactivity toward water compared to the amidinate complexes. Furthermore, the Ce complexes are more reactive compared to the Yb complexes, indicating even a reactivity towards oxygen potentially exploitable for ALD purposes. As a representative precursor, the highly reactive [Ce(dpdmg)3 ] 1 was used for proof‐of‐principle ALD depositions of CeO2 thin films using water as co‐reactant. The self‐limited ALD growth process could be confirmed at 160 °C with polycrystalline cubic CeO2 films formed on Si(100) substrates. This study confirms that moving towards nitrogen‐coordinated rare‐earth complexes bearing the guanidinate and amidinate ligands can indeed be very appealing in terms of new precursors for ALD of rare earth based materials. Abstract : Systematic engineering of Ce and Yb based amidinate and guanidinate complexes resulted in precursors suitable for atomic layer deposition (ALD) applications. Computational modeling reveals the reactivity of the complexes towards water and oxygen. A water assisted ALD process for the growth of CeO2 thin films was demonstrated with the Ce tris‐guanidinate precursor.